2013
DOI: 10.1073/pnas.1305372110
|View full text |Cite
|
Sign up to set email alerts
|

Long-term fate of nitrate fertilizer in agricultural soils

Abstract: Increasing diffuse nitrate loading of surface waters and groundwater has emerged as a major problem in many agricultural areas of the world, resulting in contamination of drinking water resources in aquifers as well as eutrophication of freshwaters and coastal marine ecosystems. Although empirical correlations between application rates of N fertilizers to agricultural soils and nitrate contamination of adjacent hydrological systems have been demonstrated, the transit times of fertilizer N in the pedosphere-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
308
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 550 publications
(362 citation statements)
references
References 46 publications
(51 reference statements)
17
308
1
8
Order By: Relevance
“…4a). This result is consistent with a long-term field study using a 15 N tracer that showed 8-12 % of the applied 15 N fertilizer was exported to the hydrosphere in the succeeding 30-year period (Sebilo et al 2013). The majority (~95 %) of riverine export of annual NANI occurred in the succeeding 10 years (Fig.…”
Section: Cause Of the Lag Effect On Riverine N Exportsupporting
confidence: 90%
See 2 more Smart Citations
“…4a). This result is consistent with a long-term field study using a 15 N tracer that showed 8-12 % of the applied 15 N fertilizer was exported to the hydrosphere in the succeeding 30-year period (Sebilo et al 2013). The majority (~95 %) of riverine export of annual NANI occurred in the succeeding 10 years (Fig.…”
Section: Cause Of the Lag Effect On Riverine N Exportsupporting
confidence: 90%
“…2014). Nitrogen leaching from legacy sources has been recognized as a primary reason for these limited results, due to the long lag time (ranging from years to decades) elapsed between watershed N inputs and riverine export (Sebilo et al 2013;Sanford and Pope 2013;Tesoriero et al 2013). Exceedance of water quality targets has prompted regulatory agencies to reevaluate nutrient management standards, measures, and guidelines (Sharpley et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sebilo et al (1) provide a unique long-term record of 15 NO 3 fertilizer fate that demonstrates N molecules from a discrete fertilizer application are transferred to soil organic matter (SOM) and subsequently mineralized over the course of approximately 100 y, during which they contribute to NO 3 leaching. The authors conclude "attempts to reduce agricultural nitrate contamination of aquatic systems must consider the long-term legacy of past applications of synthetic fertilizers" (1). Furthermore, Sebilo et al suggest that a recent decrease in anthropogenic N inputs to the Mississippi River Basin, without a concomitant decrease in riverine NO 3 loads, is consistent with their conclusion.…”
mentioning
confidence: 99%
“…For this reason the splitting of the nitrogen application rate is recommended for an efficient use of fertilizer-N (López-Bellido et al 2012). Nevertheless in the last years an increasing diffuse nitrate loading of surface water and groundwater has emerged as a major problem in many agricultural areas of the world, resulting in contamination of drinking water resources (Sebilo et al 2013). An option to minimize nitrate leaching is the use of ammonium-containing N fertilizers.…”
mentioning
confidence: 99%